2018
DOI: 10.1017/s0033291718003367
|View full text |Cite
|
Sign up to set email alerts
|

Bias-contingent attention bias modification and attention control training in treatment of PTSD: a randomized control trial

Abstract: Background. Randomized control trials (RCTs) comparing attention control training (ACT) and attention bias modification (ABM) in posttraumatic stress disorder (PTSD) have shown mixed results. The current RCT extends the extant literature by comparing the efficacy of ACT and a novel bias-contingent-ABM (BC-ABM), in which direction of training is contingent upon the direction of pre-treatment attention bias (AB), in a sample of civilian patients with PTSD. Methods. Fifty treatment-seeking civilian patients wit… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

4
46
3
2

Year Published

2019
2019
2024
2024

Publication Types

Select...
6
1

Relationship

2
5

Authors

Journals

citations
Cited by 54 publications
(55 citation statements)
references
References 62 publications
4
46
3
2
Order By: Relevance
“…While attempting to address this by including depressive symptoms and a functioning measure, many other non-symptoms may play a causal role in PTSD, as well as in bridging PTSD and other disorders (Jones et al, 2017). These may include, among others, threat-related cognitive biases (Lazarov et al, 2018(Lazarov et al, , 2019, neural abnormalities (O'Doherty et al, 2015;Koch et al, 2016), social functioning (Wilcox, 2010), and other factors which have been implicated in PTSD such as age (Konnert and Wong, 2015) and gender (Lehavot et al, 2018). Thus, future network-based research should include additional non-symptom nodes to enrich our understanding of PTSD (Jones et al, 2017).…”
mentioning
confidence: 99%
“…While attempting to address this by including depressive symptoms and a functioning measure, many other non-symptoms may play a causal role in PTSD, as well as in bridging PTSD and other disorders (Jones et al, 2017). These may include, among others, threat-related cognitive biases (Lazarov et al, 2018(Lazarov et al, , 2019, neural abnormalities (O'Doherty et al, 2015;Koch et al, 2016), social functioning (Wilcox, 2010), and other factors which have been implicated in PTSD such as age (Konnert and Wong, 2015) and gender (Lehavot et al, 2018). Thus, future network-based research should include additional non-symptom nodes to enrich our understanding of PTSD (Jones et al, 2017).…”
mentioning
confidence: 99%
“…In addition, many treated patients with ASD still develop PTSD (Kornør et al, 2008), creating a need for alternative treatments. Here, we test the efficacy of attention control therapy (ACT), a novel computerized intervention for PTSD (Badura‐Brack et al, 2015; Lazarov et al, 2019), in reducing risk for PTSD among patients with ASD. The delivery of ACT does not require highly trained therapists, it is less emotionally demanding than many psychotherapies, and has a high dissemination potential, especially for individuals who are physically disabled or immobile following trauma (Amstadter, Broman‐Fulks, Zinzow, Ruggiero, & Cercone, 2009).…”
Section: Introductionmentioning
confidence: 99%
“…Four randomized trials directly contrasted the efficacy of ABM and ACT for PTSD (Badura‐Brack et al, 2015; Lazarov et al, 2019; Schoorl, Putman, & Van Der Does, 2013). Schoorl et al (2013) found ACT and ABM to be equally effective for PTSD symptoms.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Attentional control training is an approach to attention modification that is believed to exert effects upon temporal dynamics of AB by enhancing attentional control (Badura-Brack et al, 2015). This training method, which is similar to control conditions in most attention bias modification studies, was more effective at decreasing PTSS compared to the usual look-away threat ABM (Badura-Brack et al, 2015) and bias-contingent ABM (Lazarov et al, 2018). Attentional control training does not train attention in a specific direction (i.e., towards or away from threat) but instead implicitly encourages participants to ignore the spatial locations of threatening stimuli to perform optimally on the task.…”
Section: Discussionmentioning
confidence: 99%